An altered endometrial CD8 Tissue Resident memory T cell population in recurrent miscarriage - Southcombe, J; Mounce, G; McGee, K; Elghajiji, A; Brosens, J; Quenby, S; Child, T; Granne, I (Nature Publishing Group, 2017)
When trying to conceive 1% of couples have recurrent miscarriages, defined as three or more consecutive pregnancy losses. This is not accounted for by the known incidence of chromosomal abnormality in miscarriage, and it has been suggested that there is an immunological aetiology. The endometrial mucosa is populated by a variety of immune cells which in addition to providing host pathogen immunity must facilitate pregnancy. Here we characterise the endometrial CD8-T cell population during the embryonic window of implantation and find that the majority of cells are tissue resident memory T cells with high levels of CD69 and CD103 expression, proteins that prevent cells egress. We demonstrate that unexplained recurrent miscarriage is associated with significantly decreased expression of the T-cell co-receptor CD8 and tissue residency marker CD69. These cells differ from those found in control women, with less expression of CD127 indicating a lack of homeostatic cell control through IL-7 signalling. Nevertheless this population is resident in the endometrium of women who have RM, more than three months after the last miscarriage, indicating that the memory CD8-T cell population is altered in RM patients. This is the first evidence of a differing pre-pregnancy phenotype in endometrial immune cells in RM.